The Isle of Illusion - Rodda, Emily (Rodda, Emily. Deltora shadowlands, 2002)
Lief, Barda, and Jasmine are desperately searching for the three parts of the fabled Pirran Pipe, their only hope of saving the Deltorans from the evil Shadow Lord.